High Glucose Aggravates Cholesterol Accumulation in Glomerular Endothelial Cells Through the LXRs/LncRNAOR13C9/ABCA1 Regulatory Network - Wang, Yao; Xiao, Shumin; Zhou, Saijun; Zhang, Rui; Liu, Hongyan; Lin, Yao; Yu, Pei (Frontiers in Physiology, 2020)
Background: The underlying mechanisms by which diabetes and dyslipidemia contribute to diabetic nephropathy (DN) are not fully understood. In this study, we aimed to investigate the role of high glucose (HG) on intracellular cholesterol accumulation in glomerular endothelial cells (GEnCs) and its potential mechanism. Methods: Oil red O staining, RT-qPCR, Western blotting and Immunocytofluorescence analyses were used to determine cholesterol accumulation and the expressions of LXRs and ABCA1 in GEnCs under high cholesterol and/or high glucose conditions, and the effect of these treatments was compared to that of low glucose without adding cholesterol. LncRNA microarrays were used to identify a long noncoding RNA (LncRNA OR13C9), of which levels increased in cells treated with the LXR agonist, GW3965. Fluorescence in situ hybridization (FISH) was conducted to confirm subcellular localization of LncOR13C9 and a bioinformatics analysis was used to identify competing endogenous RNA (ceRNA) regulatory networks between LncOR13C9 and microRNA-23a-5p (miR-23a-5p). Gain and loss-of-function, rescue assay approaches and dual-luciferase reporter assay were conducted to study interactions between LncOR13C9, miR-23a-5p and ABCA1. Results: We showed that HG could decrease the response ability of GEnCs to cholesterol load. Specifically that HG could downregulate LXRs expression in GEnCs under cholesterol load, and that the decrease in LXRs expression suppressed ABCA1 expression and increased cholesterol accumulation. We focused on the targets of LXRs and identified a long non-coding RNA (LncOR13C9) that was downregulated in GEnCs grown in HG and high cholesterol (HC) conditions, compared with that grown in HC conditions. We speculated that LncRNAOR13C9 was important for LXRs to increase cholesterol efflux via ABCA1 under HC. Furthermore, using gain of-function, loss-of-function and rescue assay approaches, we showed that LncOR13C9 could regulate ABCA1 by inhibiting the action of miR-23a-5p in the LXR pathway. Furthermore, dual-luciferase reporter assay was conducted to study the interaction of LncOR13C9 with miR-23a-5p. Conclusions: Overall, our study identified the LXRs/LncOR13C9/ miR23A-5p/ABCA1 regulatory network in GEnCs, which may be helpful to better understand the effect of high glucose on cholesterol accumulation in GEnCs under cholesterol load and to explore new therapeutic tools for the management of DN patients.